Qualités physicochimiques et nutritionnelles du blé fermenté type « El Hamoum ». Aptitudes à la transformation en Couscous - BEHIH, Wahib; BENZIANE, Abdelhaq (My University, 2022)
The objective of our study is to identify the influence of harvesting areas on the physicochemical qualities of fermented wheat (hamom) and by-product derived couscous. According to our results we have found that the polyphenols content of fermented wheat of wilaya of Tiaret is more important compared to other wilaya which estimated at 5.78 mg EAG/ml, While the result of wilaya of Chelf are estimated by 1.93 mg EAG/ml The results reveal the relapse of the fermented couscous of the wilaya of Tiaret in flavonoids with a content estimated by 14.47 mg AQ/ml compared to the wilaya of Chlef 6.45 mg EQ/ml
Keywords: wheat; hamoum; couscous; polyphenols; flavonoids